Effects of Caffeine on Skin and Core Temperatures, Alertness, and Recovery Sleep During Circadian Misalignment. (April 2014) - McHill, Andrew W.; Smith, Benjamin J.; Wright, Kenneth P.
Caffeine promotes wakefulness during night shift work, although it also disturbs subsequent daytime sleep. Increased alertness by caffeine is associated with a higher core body temperature (CBT). A lower CBT and a narrow distal-to-proximal skin temperature gradient (DPG) have been reported to be associated with improved sleep, yet whether caffeine influences the DPG is unknown. We tested the hypothesis that the use caffeine during nighttime total sleep deprivation would reduce the DPG, increase CBT and alertness, and disturb subsequent daytime recovery sleep. We also expected that a greater widening of the DPG prior to sleep would be associated with a greater degree of sleep disturbance. Thirty healthy adults (9 females) aged 21.6 ± 3.5 years participated in a double-blind, 28-h modified constant routine protocol. At 23 h of wakefulness, participants in the treatment condition ( n = 10) were given 2.9 mg/kg caffeine, equivalent to ~200 mg (or 2 espressos) for a 70-kg adult, 5 h before a daytime recovery sleep episode. Throughout the protocol, core and skin body temperatures, DPG, sleep architecture, and subjective alertness and mood were measured. Prior to sleep, caffeine significantly widened the DPG and increased CBT, alertness, and clear-headedness ( p < 0.05). Caffeine also disturbed daytime recovery sleep ( p < 0.05). Increased CBT and a wider DPG prior to sleep were associated with a longer latency to sleep, and a wider DPG was associated with disturbed recovery sleep (i.e., increased wakefulness after sleep onset, increased stage 1 sleep, decreased sleep efficiency, and decreased slow wave sleep) ( p < 0.05). A widening of the DPG following nighttime caffeine may represent a component of the integrated physiological response by which caffeine improves alertness and disturbs subsequent daytime recovery sleep. Furthermore, our findings highlight that sleep disturbances associated with caffeine consumed near the circadian trough of alertness are still present when daytime recovery sleep occurs 5 h or approximately 1 half-life later.